Fabrication of solid lipid nanoparticles by hot high shear homogenization and optimization by Box–Behnken design: An accelerated stability assessment - Amit Kumar Singh&, Alok Mukerjee&, Himanshu Pandey, Shanti Bhushan Mishra& (Journal of Applied Pharmaceutical Science, 2021)
In the present study, an attempt was made to fabricate Miconazole nitrate (MCN)-loaded solid lipid nanoparticles (SLN) by hot high shear homogenization method (HSHM). Box–Behnken design (BBD) was employed as an experimental design to optimize the formulations consisting of three levels, four factors, and three center points. The design matrix of BBD consisted of 27 runs by employing 5 responses, i.e., average particle size, polydispersity index, zeta potential, percent encapsulation efficiency, and percent drug loading. The four factors selected were drug:tristearin (% w/w), Tween 80 (% w/v), homogenization speed (rpm), and homogenization time (minutes). Contour plots and 3D response surface plots were generated. The MCN-loaded optimized SLN formulation was prepared by setting the formulation factors of hot HSHM according to the solution given by BBD at a drug:tristearin ratio of 7.3727 (%w/w), Tween 80 concentration of 15% (w/v), homogenization speed of 17,000 rpm, and homogenization time of 20 minutes. The optimized formulation was subjected to differential scanning calorimetry, Fourier transform infrared spectroscopy, and field emission scanning electron microscopy study. In vitro drug release kinetic study of optimized formulation followed the Korsmeyer–Peppas model (regression coefficient value of 0.945) and it was found to be stable for 6 months at 5°C ± 3°C. These results reveal the successful development of MCN-loaded SLN by hot HSHM.
Keywords: Box–Behnken design, high shear homogenization method, miconazole nitrate, solid lipid nanoparticles.